Peran Lembaga Keuangan Mikro Syariah (BMT) Dalam Percepatan Pertumbuhan Usaha Mikro Di Kota Jambi - M. Khoirullah; A. A. Miftah; Ahsan Putra Hafiz (International Forum of Researchers and Lecturers, 2025)
This study aims to (1) to find out how the role of Islamic microfinance institutions on micro businesses in Jambi city. (2) to find out how the development of Islamic microfinance institutions in Jambi city. (3) to find out what efforts are made by Islamic microfinance institutions (BMT) to increase their role towards micro enterprises in Jambi city. The problems discussed in this thesis are (1) how the role of Islamic microfinance institutions on micro businesses in Jambi city. (2) what influences the role of Islamic microfinance institutions (BMT) on micro businesses. (3) what efforts are made by Islamic microfinance institutions (BMT) to increase their role towards micro business ventures in Jambi city. The research method used is descriptive qualitative. The descriptive method of analysis is obtained through data sourced from observation, interviews, and documentation as well as other sources that support field research by finding data sources directly from the field, namely from the BMT through data collection and interviews with the parties concerned. The results of this study are the Financing mechanism at BMTs in Jambi city, namely BMT Al-Ishlah, BMT KOSSUMA, and BMT. Muslimah Masyitoh tends to be the same, the difference lies only in the tax year of the vehicle financing ceiling, and the length of installments. Financing includes several contracts, namely murabahah, ijarah, ar-Rahn, mudharabah, musyarakah and qordhul hasan. Analysis before channeling financing at BMT for prospective financing members includes: Character, Capital, Capacity, Condition, and Coleterol. The importance of Islamic microfinance by BMTs in Jambi city in empowering MSMEs is evidenced by the main target of BMT financing is small business actors who are not reached by banks. Simple procedures and applied financing are needed by Jambi city MSMEs in developing their businesses. The constraints of the Jambi city BMT cooperative in carrying out its business, namely financing in the context of empowering MSEs, include internal constraints and external constraints.